Portion size effects on weight gain in a free living setting - French, Simone A (2014)
OBJECTIVE: Examine the effect of weekday exposure over six months to different lunch sizes on energy intake and body weight in a free-living sample of working adults. DESIGN AND METHODS: Adults (n=233) were randomly assigned to one of three lunch size groups (400 kcal; 800 kcal; 1600 kcal) or to a no-free lunch control group for six months. Weight and energy intake were measured at baseline, and months 1, 3, and 6. RESULTS: Lunch energy was significantly higher in the 800 and 1600 kcal groups compared to the 400 kcal group (p < 0.0001). Total energy was significantly higher for the 1600 kcal group compared to the 400 and 800 kcal groups (p = 0.02). Body weight change at six months did not significantly differ at the 5% level by experimental group (1600 kcal group: +1.1 kg (sd=0.44); 800 kcal group: −0.1 kg (sd=0.42); 400 kcal group: −0.1 kg (sd=0.43); control group: 1.1 (sd=0.42); p=.07). Weight gain over time was significant in the 1600 kcal box lunch group (p < 0.05). CONCLUSIONS: Weekday exposure for six months to a 1600 kcal lunch caused significant increases in total energy intake and weight gain.